Bangladesh : Report on the Observance of Standards and Codes; Fiscal Transparency Module; Update. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for Bangladesh. The paper discusses that the authorities have implemented a number of measures recommended in the ROSC, particularly those aimed at establishing reliable fiscal reports, and have moved toward establishing an effective basis for medium-term budgeting. Progress on longer-term issues with regard to improving reporting and control over quasi-fiscal activities of state-owned enterprises and strengthening government watchdog institutions will require continuing sustained effort.